Iceland : tectonics, volcanics, and glacial features - Jovanelly, Tamie J. (Geophysical monograph, 2020)
Explore the dramatic forces that have shaped the Icelandic landscape over 30 million years Iceland's formation and ongoing evolution offers a masterclass in geophysical processes. Iceland: Tectonics, Volcanics, and Glacial Features presents a regional guide to the landscape of this unique island. Accessible to academics, students, novice geologists, and tourists alike, chapters reflect the most popular way to explore the island, beginning in the southwest region and ending in the northwest.'' Volume highlights include: -An overview of Iceland's geologic history -Exploration of the dynamic tectonic setting that has shaped the island -Descriptions of landscape features of active and extinct volcanoes -Discussion of the impact of glaciation in the past and present -Techniques for monitoring geologic hazards -Developments in harnessing geothermal energy The American Geophysical Union promotes discovery in Earth and space science for the benefit of humanity.'Its publications disseminate scientific knowledge and provide resources for researchers, students, and professionals.